2013
DOI: 10.1149/2.103309jes
|View full text |Cite|
|
Sign up to set email alerts
|

An Experimental Study of the Effects of Operational History on Activity Changes in a PEMFC

Abstract: The accurate evaluation of the activation overpotential of a membrane electrode assembly (MEA) is essential for fuel cell design. We have developed a new method of precisely determining the activity of cathode catalyst layer in MEA by maintaining the effect of platinum oxides at a constant level and have subsequently studied activity changes resulting from various operational histories. Cyclic voltammetry was used to quantitatively correlate activity changes in the cathode catalyst layer with various operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
91
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(96 citation statements)
references
References 38 publications
4
91
1
Order By: Relevance
“…On the other hand, the metal content in ZrO 2 , Fe 0.17 Zr 0.83 O 1.91 , and Fe 0.07 Zr 0.93 O 1.97 (2 nd , 3 rd , and 4 th row) is only approximately half of the nominally expected value. This discrepancy is likely due to the carbon produced by decomposition of the Zr precursor, which is significantly larger in comparison to that produced in the Fe sample, since the amount of FePc(t-Bu) 4 is ≈70 times lower than the ZrCl 2 Pc(t-Bu) 4 . Although the absolute amount of Fe and ZrO 2 in Fe 0.17 Zr 0.83 O 1.91 , and Fe 0.07 Zr 0.93 O 1.97 is 50% of the expected, the atomic ratios between them are still the same as theoretical.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, the metal content in ZrO 2 , Fe 0.17 Zr 0.83 O 1.91 , and Fe 0.07 Zr 0.93 O 1.97 (2 nd , 3 rd , and 4 th row) is only approximately half of the nominally expected value. This discrepancy is likely due to the carbon produced by decomposition of the Zr precursor, which is significantly larger in comparison to that produced in the Fe sample, since the amount of FePc(t-Bu) 4 is ≈70 times lower than the ZrCl 2 Pc(t-Bu) 4 . Although the absolute amount of Fe and ZrO 2 in Fe 0.17 Zr 0.83 O 1.91 , and Fe 0.07 Zr 0.93 O 1.97 is 50% of the expected, the atomic ratios between them are still the same as theoretical.…”
Section: Resultsmentioning
confidence: 95%
“…However, low-loaded Pt electrodes are known to exhibit performance losses originating from mass-transport limitations, which have been assigned primarily to oxygen transport resistances occurring at the Pt/ionomer interface. 4,5 In addition, Kongkanand and Mathias 6 have reported that a decrease of the noble metal loading to below 100 μg Pt /cm 2 geo results in an increase in the stack cost since below this loading other stack components like the bipolar plates, the gas diffusion layer, the membrane as well as system components need further improvements and become more costly. Thus, current ORR catalyst research for PEMFCs is mainly driven by developing either highly active Pt-alloy catalysts or active and cost-effective platinumgroup-metal-free (PGM-free) catalysts.…”
mentioning
confidence: 99%
“…While ECSA measurement only requires electron and proton access, good access to reactant O 2 is also required for ORR. Minor changes in the ionomer distribution in the electrode have been shown to significantly affect the ORR activity as well as fuel cell performance at high current density, 3,35,[37][38][39][40][41][42] a topic of great interest in the fuel cell community. 3,43,44 Therefore, it is not a surprise that these vastly diverse methods yield slightly different performance.…”
Section: Resultsmentioning
confidence: 99%
“…Hypothetically, the local resistance can be attributed to slow oxygen dissolution process at the gas/ionomer interface, 266,338 and/or strong interaction between the Pt surface and the sulfonate groups in ionomer leading to either a decrease in the effective Pt surface area, or ionomer structural changes in the thinfilms near the Pt surface that lowers oxygen permeability as discussed below. 340 Thus, the measured local resistance is a sum of three components from gas phase to the Pt surface: the interfacial resistance at the gas/ionomer interface, the bulk resistance of the ionomer film, and the interfacial resistances at ionomer/Pt interfaces. Quantification of each resistance would provide fundamental knobs to mitigate the voltage losses due to the local resistance via a combined modeling and experimental approach.…”
Section: 142mentioning
confidence: 99%